ExoMol molecular line lists – XX. A comprehensive line list for H3+. Issue 2 (28th February 2017) - Mizus, Irina I.; Alijah, Alexander; Zobov, Nikolai F.; Lodi, Lorenzo; Kyuberis, Aleksandra A.; Yurchenko, Sergei N.; Tennyson, Jonathan; Polyansky, Oleg L.
Abstract: H$_3^+$ is a ubiquitous and important astronomical species whose spectrum has been observed in the interstellar medium, planets and tentatively in the remnants of supernova SN1897a. Its role as a cooler is important for gas giant planets and exoplanets, and possibly the early Universe. All this makes the spectral properties, cooling function and partition function of H$_3^+$ key parameters for astronomical models and analysis. A new high-accuracy, very extensive line list for H$_3^+$ called MiZATeP was computed as part of the ExoMol project alongside a temperature-dependent cooling function and partition function as well as lifetimes for excited states. These data are made available in electronic form as supplementary data to this article and at www.exomol.com .